Balingkang Kintamani Festival, Chinese Tourists, and the Collective Memory of the Balinese - Wijaya, I Nyoman (History Department, Semarang State University and Historian Society of Indonesia, 2022)
Balingkang Kintamani Festival is a cultural parade held in Bali during 2019 Chinese New Year holiday. The main purpose of this festival was to increase the number of tourist visits from China, which had sharply declined due to the lawsuit against super cheap package tour to Bali, followed by the closure of illegal and semi-legal shops owned by citizens of China in Bali in 2018. Balingkangis a temple of worship in Bangli Regency, estimated to be as old as the kingdom of King Jayapangus (1177-1182 AD), who is said to have had a princess of China as his wife. This narrative, however, is not supported by adequate historical evidence. King Jayapangus had never established cultural, political, and trade relations with China,and thus he cannot have had a wife of a Chinese princess. Consequently, the narrative of the past in the festival seems to have been falselynarrated. This article wishes to demonstrate how the interests of the present has dictated the narrative of the past, and how this has affected the collective memory of the Balinese people regarding the Chinese community in Bali.Balingkang Kintamani Festival adalah sebuah parade budaya yang diselenggarakan di Bali pada liburan Imlek 2019. Tujuan utama Festival ini untuk membidik kunjungan wisatawan asal Tiongkok, yang sempat menurun tajam sejak munculnya gugatan terhadap kasus paket wisata super murah di Tiongkok untuk tujuan Bali, disusul penutupan toko-toko ilegal dan semi legal milik warga Tiongkok di Bali pada 2018. Balingkang adalah sebuah kuil pemujaan di Kabupaten Bangli, diperkirakan sezaman dengan masa pemerintahan Raja Jayapangus (1177-1182), yang dikisahkan memiliki istri seorang putri Tiongkok. Akan tetapi narasi ini tidak didukung bukti-bukti sejarah yang memadai. Raja Jayapangus tidak pernah menjalin hubungan dagang, politik, dan budaya dengan Tiongkok,dan karena itu tidak mungkin beristrikan puteri Tiongkok. Jadi, narasi masa lalu dalam festival itu tampak sangat dipaksakan. Artikel ini ingin menunjukkan bagaimana kepentingan masa kini mendikte narasi masa lalu, serta bagaimana implikasinya atas memori kolektif masyarakat Bali terhadap komunitas Tionghoa di Bali. Cite this article: Wijaya, I N. (2022). Balingkang Kintamani Festival, Chinese Tourists, and the Collective Memory of the Balinese. Paramita: Historical Studies Journal, 32(1), 67-77. http://dx.doi.org/10.15294/paramita.v32i1.31857